Eclipse - Meyer, Stephenie, 1973- (London : Atom, 2010)
" 'Bella?' Edward's soft voice came from behind me. I turned to see him spring lightly up the porch steps, his hair windblown from running. He pulled me into his arms at once, and kissed me again. His kiss frightened me. There was too much tension, too strong an edge to the way his lips crushed mine - like he was afraid we had only so much time left to us. As Seattle is ravaged by a string of mysterious killings and a malicious vampire continues her quest for revenge, Bella once again finds herself surrounded by danger. In the midst of it all, she is forced to choose between her love for Edward and her friendship with Jacob - knowing that her decision has the potential to ignite the ageless struggle between vampire and werewolf. With her graduation approaching, Bella has one more decision to make: life or death. But which is which? Following the international bestsellers Twilight and New Moon, Eclipse is the much-anticipated third book in Stephenie Meyer's captivating saga of vampire romance."
-- Evasion -- Motives -- Nature -- Imprint -- Switzerland -- Unhappy ending -- Temper -- Target -- Scent -- Legends -- Time -- Newborn -- Declaration -- Wager -- Epoch -- Alliance -- Instruction -- Selfish -- Compromise -- Trails -- Fire and ice -- Monster -- Snap decision -- Mirror -- Ethics -- Needs.
Keywords: Vampires -- Juvenile fiction; Werewolves -- Juvenile fiction; High schools -- Juvenile fiction